In vitro Inhibitory Activity of Ethanolic Fruit Extract from Averrhoa bilimbi L. against Streptococcus pyogenes Bacteria - Puspita Dewi; Gusti Ayu Ratih; Burhannuddin Burhannuddin; Gede Sudarmanto (Health Notions, 2019)
Averrhoa bilimbi L., popularly known as belimbing wuluh, is a common plant used as traditional medicine and cooking ingredients in Indonesia. Averrhoa bilimbi fruit contains many active substances as antibacterial such as tannin, formic acid, flavonoids, saponins, peroxides, and triterpenoids. Streptococcus pyogenes is a pathogenic bacteria that can cause respiratory infections. This study was carried out to investigate the inhibitory activity of Averrhoa bilimbi L. fruit extract at various concentrations on the growth of Streptococcus pyogenes. This study was a true experimental with post test only control design. The inhibitory activity was assessed by the KirbyBauer’s disc diffusion method with four different extract concentrations (20%, 40%, 60%, 80%), 96% EtOH as negative control, and Amoxicillin antibiotic as positif control. The EtOH extract showed the mean diameter of inhibition zone of 20% extract was 11.43 mm (strong), 40% extract was 19.13 mm (strong), 60% extract was 24.58 mm (very strong), 80% extract was 30.99 mm (very strong), and the negative control (96% EtOH) was 0.00 mm. Least Significant Difference test showed there were significant different of inhibition zone in each extract concentrations of Averrhoa bilimbi L. against Streptococcus pyogenes with the strongest inhibitory activity is 80% extract concentration. Keywords: Averrhoa bilimbi, Inhibitory activity, Streptococcus pyogenes